Antimicrobial and Immunomodulatory Action of Probiotic Composition of Bacilli on Bacterial Vaginitis in Mice - Lazarenko, L.M.; Babenko, L.P.; Safronova, L.A.; Demchenko, O.M.; Bila, V.V.; Zaitseva, G.M.; Spivak, M.Ya.; Лазаренко, Л.М.; Бабенко, Л.П.; Сафронова, Л.А.; Демченко, О.М.; Біла, В.В.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The purpose of this study was to investigate the antimicrobial and immunomodulatory action of a probiotic composition of Bacillus subtilis and B. megatherium strains (UnicaUro, Sirion (Ukraine)) for experimental bacterial vaginitis. Methods. Experimental studies were conducted on female BALB/c mice; we used Staphylococcus aureus strain B-918 (ATCC 6538) to induce bacterial vaginitis. The strain was vaginally introduced into mice before treatment with probiotic bacteria. In the vagina of mice, aerobic and optionally anaerobic bacteria, including representatives of the genera Staphylococcus, Streptococcus, Lactobacillus, Bifidobacterium, Pseudomonas, coliform bacteria, and microscopic fungi were identified in different periods of observation using generally accepted microbiological methods. Serum antibody titer to S. aureus was determined by the bacterial agglutination reaction. The phagocytic activity and oxygen-dependent bactericidal activity of peritoneal exudate macrophages (PEM) were evaluated using generally accepted immunological methods. Results. The formation of bacterial vaginitis in the BALB/c mice line infected with S. aureus B-918 (ATCC 6538) was evidenced by the appearance of external clinical manifestations of the infectious and inflammatory process against the background of the increased number of aerobic and optionally anaerobic microorganisms, including representatives of the genus Staphylococcus and Streptococcus, microscopic fungi, and decreased number of lactobacilli in different observation periods. The probiotic introduction to mice with bacterial vaginitis led to a dynamic change in the vaginal microbiota: the number of aerobic and optionally anaerobic microorganisms decreased, primarily due to the normalization of the number of representatives of Staphylococcus genus accompanied by a decrease in the antibody titer to staphylococcus in the blood serum. The effective therapeutic action of the probiotic was confirmed by the gradual disappearance of the external clinical signs of the infectious-inflammatory process in the vagina against the background of the functional activity of PEM. Conclusions. The probiotic composition of B. subtilis and B. megatherium (UnicaUro, Sirion, Ukraine) is a promising antimicrobial formulation that may be used in the treatment of bacterial vaginitis; however, further studies are required to confirm its therapeutic, antimicrobial, and immunomodulatory efficacy.